Design optimization of a solar tower power plant heliostat field by considering different heliostat shapes. (15th August 2020) - Belaid, Abdelfetah; Filali, Abdelkader; Gama, Amor; Bezza, Badreddine; Arrif, Toufik; Bouakba, Mustapha
Summary: The present study focuses on the optimization of solar tower power plant heliostat field by considering different heliostat shapes including rectangular, square, pentagon, hexagon, heptagon, octagon, and circular heliostat shapes. The optimization is carried out using an in‐house developed code‐based MATLAB program. The developed in‐house code is validated first on a well‐known PS10 Solar Thermal Power plant having rectangular heliostats shape and the resulting yearly unweighted heliostat field efficiency of about 64.43% could be obtained. The optimized PS10 heliostat field using different heliostat shapes showed that the circular and octagon heliostat shapes provide better efficiency with minimum land area. The yearly efficiency is increased from 69.65% for the rectangular heliostat shape to 70.96% and 71% for the octagon and circular shapes, respectively. In addition, the calculated field area (land area) is reduced for the case of circular and octagon heliostat shapes with a gain of about 11.10% and 10.93% (about 42.0436 × 10 3 and 41.4036 × 10 3 m 2 ), respectively, in comparison with the PS10 field area. Abstract : Optimized PS10 heliostat field for different heliostat shapes. Results showed that the circular and octagon shapes provide better efficiency with minimum land area. Field efficiency increased from 69.65% for the rectangular shape to 70.958% and 70.991% for the octagon and circular heliostat shapes. Field area reduced about 10.93% and 11.10% for octagon and circular heliostat shapes in comparison with the rectangular shape. The novelty of the present work lies in the development and optimization of heliostat field based different heliostats shapes by minimum blocking and shadow effect and to guarantee a high field efficiency with minimum field land.